Covid-19 pandemic as an aggravating factor of health inequalities - Stachteas, Panagiotis; Stachteas, Fotis (The Greek Review of Social Research, 2020)
The rapidly spreading Covid-19 pandemic has had unprecedented implications on the world's population by decisively affecting human lives, cultures and economies. Although its social neutrality had initially been argued, clear differences in mortality and morbidity were soon confirmed, reflecting pre-existing health inequalities. The financially poor, the racial minorities, the refugees, the homeless are affected more often and more seriously by the pandemic, intensifying their already burdened health profile. In addition, the economy has been irreparably damaged, unemployment rates have risen and many households were led to poverty. Finally, health policies have a key role to play in both avoiding the deterioration of existing social inequalities and shaping an equal, just and solidary world.